Therapy of group acceptance and commitment: experience in a public service of mental health - Ruiz Sánchez, Juan José (2017)
It presents a summary of the fundamental aspects of the three generations of behavioral therapy. Third generation therapy is highlighted, the role of behavioral functions in their context (especially language). It raises the empirical foundations and applications of the Group Contextual Therapies based on its effectiveness and efficiency usually in public services of psychological attention. The main work focuses on Group Acceptance and Commitment Therapy and in reference to "realizing" or discriminating as a way of deriving responses to meaningful actions with meaning in people's lives and finally summarized our experience of how we work with Acceptance and Commitment Therapy Group to anxiety-depressive problems in our context of public mental health care.